The Role of Religiosity in Moderating Auditor Integrity - Cahyadi, Prematur Alfian; Malakiano, Reskino (Indonesian Scientific Publication, 2025)
This study investigates the influence of Time Budget Pressure, Auditor Experience, and Auditor Commitment on Auditor Integrity, with Religiosity introduced as a moderating variable. The research is motivated by the need to understand how ethical and experiential factors interact to shape auditor behavior, particularly in contexts where integrity is paramount. A quantitative approach was employed through the distribution of structured questionnaires. The sampling technique used was non-probability sampling, targeting auditors from various professional backgrounds, including public accounting firms, internal corporate audit units, government internal auditors, and external government auditors. The key variables measured include Time Budget Pressure, Auditor Experience, Auditor Commitment, Religiosity, and Auditor Integrity. The findings reveal that both Time Budget Pressure and Auditor Experience significantly influence Auditor Integrity. Furthermore, Religiosity moderates the relationship between these two variables and Auditor Integrity. In contrast, Auditor Commitment does not exhibit a significant effect on Auditor Integrity, and Religiosity does not moderate this particular relationship. The inclusion of Religiosity as a moderating variable offers a novel contribution to the literature on auditor ethics and behavioral influences. The results suggest that fostering religiosity among auditors may enhance integrity, particularly under conditions of time pressure or varying levels of experience. These insights have theoretical implications for the development of ethical frameworks and practical relevance for regulatory bodies and professional organizations aiming to strengthen the auditor’s code of ethics.